Docencia-investigación : ¿una relación antagónica, inexistente o necesaria? - Orler, José (2012)
There is an extensive international literature problematized referred to the teaching-research relationship multiplying approaches and approaches, from the 70s. In Argentina since the 90s the above subject is of concern to educational researchers. However, attempts to unravel the nature of this relationship are far from admitting some kind of conclusion, and even the starting assumptions and postulates are agreed. This is the topic that, as part of research aimed to study higher education, attempts to stop the look on how they occur and the two activities constitute the central and university teaching and research: how they relate, are added, enrich, complement, overlap, oppose, compete and tense, and how actors are assumed by academics and by the institutions themselves. This exposed and focused from the particular disciplinary field of law.